A degradable end group quaternary ammonium ABA block copolymer silicone oil, a preparation method and application thereof

CN122917320APending Publication Date: 2026-10-16ZHEJIANG MANSTER NEW MATERIAL TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611072195.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

专利文献CN107522866A虽然尝试了无溶剂合成路线,但产品中D4、D5、D6环状硅氧烷含量难以满足欧盟REACH法规要求(均小于1000 ppm)

Benefits of technology

(1)可控降解性:通过在聚醚间隔基链段中嵌入酯键、缩醛键或碳酸酯键等可断裂连接基团,赋予产品在特定条件(弱酸性废水、酶解)下的可控降解能力。降解产物主要为低分子量聚醚片段、硅氧烷片段和季铵盐片段,分子量小于1000 Da,可进一步被微生物分解。实验数据表明,本发明的产品在pH 5.0、37℃条件下72小时降解率可达65%以上,而不可降解对照样品在相同条件下无明显降解(<5%),差异显著。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_30
    Figure SMS_30
  • Figure SMS_40
    Figure SMS_40
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The present application relates to the field of environment-friendly organic silicon material and textile finishing technology, and particularly relates to a terminal group quaternary ammonium silicone oil with controllable degradation performance and a preparation method and application thereof; the terminal group quaternary ammonium silicone oil has a general formula (I) structure; wherein: B is a siloxane hydrophobic chain segment, and contains a repeating unit shown in formula (II): B=[Si(R1)(R2)O]_x; A and A' are hydrophilic spacer chain segments; X and X' are terminal group quaternary ammonium groups; the A and A' hydrophilic spacer chain segments are embedded with a degradable linking group L, and the degradable linking group is selected from at least one of an ester bond shown in formula (III), an acetal bond shown in formula (IV) or a carbonate bond shown in formula (V); the present application has the following beneficial effects: controllable degradation: by embedding a breakable linking group such as an ester bond, an acetal bond or a carbonate bond in a polyether spacer chain segment, the product is endowed with controllable degradation capacity under specific conditions (weak acid wastewater, enzymatic degradation).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of environmentally friendly organosilicon materials and textile finishing technology, specifically to a terminal quaternary ammonium silicone oil with controllable degradation properties, its preparation method, and its application. Background Technology

[0002] With increasingly stringent global environmental regulations, the biodegradability of textile auxiliaries has become a key focus of industry attention. The EU's REACH regulation has tightened its requirements for substances of very high concern (SVHCs), particularly reducing the limit for cyclic siloxanes (D4, D5, D6) to below 1000 ppm. Furthermore, the Swedish Chemicals Agency (KEMI) and the Norwegian Climate and Pollution Authority (KLIF) have listed certain quaternary ammonium compounds as potential environmental hazards, requiring the phase-out of persistent organosilicon compounds in detergents and textile auxiliaries.

[0003] The "Technical Specifications for Wastewater Treatment Engineering in the Textile Dyeing and Finishing Industry" issued by China's Ministry of Industry and Information Technology also sets stricter emission standards for COD and recalcitrant organic matter in wastewater. Existing quaternary ammonium silicone oils, whether side-chain or end-group types, possess highly stable C-Si and CN bonds in their molecular backbone, with half-lives reaching decades in the natural environment, posing potential ecological risks. Although some studies have attempted to improve hydrophilicity and self-emulsifying properties by introducing polyether segments, the basic molecular backbone remains non-degradable. Furthermore, the synthesis of existing products typically requires the use of large amounts of low-flash-point solvents such as isopropanol, which not only poses safety hazards but also increases the difficulty of wastewater treatment.

[0004] Patent documents CN109535428A and CN10940304A disclose methods for synthesizing block silicone oils using large amounts of isopropanol or ethylene glycol butyl ether as solvents, with solvent usage reaching 10-80% of the reaction system, resulting in significant VOC emissions. While patent document CN107522866A attempted a solvent-free synthesis route, the content of D4, D5, and D6 cyclic siloxanes in the product failed to meet the EU REACH regulations (all less than 1000 ppm).

[0005] Therefore, developing a novel quaternary ammonium silicone oil that combines excellent finishing properties, controllable degradation capability, and environmentally friendly synthesis process has significant practical importance and market value. Summary of the Invention

[0006] To address the shortcomings of existing technologies, a biodegradable quaternized ABA block copolymer silicone oil with end groups has a general formula (I) structure: XAB-A'-X' (I); where: B is a hydrophobic segment of a siloxane, containing the repeating unit shown in formula (II): B = [Si(R¹)(R²)O]_x; A and A' are hydrophilic spacer segments; X and X' are terminal quaternary ammonium groups; The hydrophilic spacer segments A and A' contain a degradable linker group L, which is selected from at least one of the ester bond shown in formula (III), the acetal bond shown in formula (IV), or the carbonate bond shown in formula (V). ; ; ; in Selected from hydrogen atoms or C1-C6 alkyl groups; The degradable linker group causes the copolymer silicone oil to degrade into fragments with a molecular weight of less than 1000 Da under acidic conditions of pH 4.0-6.5 or in the presence of esterase.

[0007] Preferably, the hydrophilic spacer segments A and A' are polycaprolactone-polyethylene glycol copolymer segments containing ester bonds, with the following structural formula: A = -(EO)_m-(CL)_n-; where EO is an ethylene oxide unit, CL is a caprolactone unit, m is 5-30, and n is 1-20.

[0008] Preferably, the X and X' terminal quaternary ammonium groups simultaneously comprise an amide ammonium group as shown in formula (VI) and a dialkyl ammonium group as shown in formula (VII): ; ;in Selected from C11-C23 straight-chain or branched, saturated or unsaturated alkyl groups. It is an anionic counterion; the molar ratio of the ammonium amide group to the dialkylammonium group is 9:1 to 6:4.

[0009] Preferably, the molar ratio of the ammonium amide group to the dialkylammonium group is 7:3.

[0010] Preferably, both R¹ and R² are methyl groups.

[0011] Preferably, x is an integer between 50 and 300.

[0012] Preferably, x is an integer between 80 and 160.

[0013] Preferably, the biodegradable quaternized ABA block copolymer silicone oil exhibits a degradation rate of not less than 50% after 72 hours under conditions of pH 5.0 and 37°C.

[0014] Preferably, the amine value of the biodegradable quaternized ABA block copolymer silicone oil is 2-60 mg KOH / g polymer.

[0015] A method for preparing a biodegradable quaternized ABA block copolymer silicone oil with terminal groups includes the following steps: Step (1): Using hydroxyl-terminated polycaprolactone-polyethylene glycol copolymer containing ester bonds as raw material, an allyl-terminated biodegradable polyether is prepared by reacting it with allyl glycidyl ether. The structural formula is as follows: ; Where m is 5-30 and n is 1-20; Step (2): In the presence of a platinum catalyst, the hydrogen-terminated silicone oil of formula (VIII) is subjected to a hydrogenation-silanization reaction with the allyl-terminated biodegradable polyether obtained in step (1) to obtain an epoxy silicone oil intermediate with biodegradable segments at the end groups: ; Where R¹ is methyl and x is 50-300; Step (3): The epoxy silicone oil intermediate and the tertiary amine are subjected to a ring-opening quaternization reaction in the presence of an acidic catalyst to obtain the degradable end-group quaternized ABA block copolymer silicone oil.

[0016] Preferably, the tertiary amine in step (3) is a mixed tertiary amine of amide amine and dialkylolamine, wherein the amide amine has the structure shown in formula (IX) and the dialkylolamine has the structure shown in formula (X): ; ; in Selected from C11-C23 alkyl groups, Selected from C1-C10 alkyl groups; The molar ratio of amide amine to dialkylolamine in the mixed tertiary amine is 9:1 to 6:4.

[0017] Preferably, the molar ratio of amide amine to dialkylolamine in the mixed tertiary amine is 7:3.

[0018] Preferably, the number-average molecular weight of the biodegradable polyether in step (1) is 500-3000 Da.

[0019] Preferably, the number-average molecular weight of the biodegradable polyether in step (1) is 800-2000 Da.

[0020] Preferably, the reaction temperature of step (1) is 60-100℃ and the reaction time is 4-12 hours; preferably, the hydrosilylation reaction temperature of step (2) is 70-120℃; and the ring-opening quaternization reaction temperature of step (3) is 70-110℃ and the reaction time is 4-24 hours.

[0021] Preferably, the reaction temperature of step (1) is 70-90℃; the reaction temperature of the hydrogenation silanization in step (2) is 80-100℃; and the reaction temperature of the ring-opening quaternization in step (3) is 80-100℃.

[0022] Preferably, the acidic catalyst in step (3) is selected from at least one of acetic acid, lauric acid, isononanoic acid, and lactic acid, and the amount used is 0.5-2.0 times the molar number of the tertiary amine.

[0023] A textile finishing agent composition comprising the aforementioned biodegradable terminal quaternized ABA block copolymer silicone oil, an emulsifier, and water.

[0024] Preferably, the composition contains 5-40% silicone oil by weight, 1-15% emulsifier by weight, 45-94% water by weight, and has a pH of 4-7.

[0025] Preferably, the composition contains 5-40% silicone oil by weight, 1-15% emulsifier by weight, 45-94% water by weight, and has a pH of 4-7.

[0026] Preferably, the application of the biodegradable quaternized ABA block copolymer silicone oil at the end groups in textile softening finishing.

[0027] Preferably, the application of the biodegradable quaternized ABA block copolymer silicone oil at the end group in the hydrophilic finishing of textiles.

[0028] Preferably, the textile, after finishing, can be degraded into fragments with a molecular weight of less than 1000 Da under waste or wastewater treatment conditions. This invention achieves the following effects: Compared with the prior art, the present invention has the following beneficial effects: (1) Controllable Degradability: By embedding cleavable linking groups such as ester bonds, acetal bonds, or carbonate bonds into the polyether spacer segments, the product is endowed with controllable degradation capability under specific conditions (weakly acidic wastewater, enzymatic hydrolysis). The degradation products are mainly low molecular weight polyether fragments, siloxane fragments, and quaternary ammonium salt fragments, with a molecular weight of less than 1000 Da, which can be further decomposed by microorganisms. Experimental data show that the product of this invention can achieve a degradation rate of more than 65% after 72 hours under pH 5.0 and 37℃ conditions, while the non-degradable control sample showed no significant degradation (<5%) under the same conditions, showing a significant difference.

[0029] (2) Performance is not compromised: The biodegradable linker groups are embedded in the polyether spacer segments and do not directly affect the function of the quaternary ammonium groups. Comparative tests show that the softness (TSA value 41.5) and hydrophilicity (drip time 3.5 seconds) of the biodegradable product of this invention are comparable to those of the non-biodegradable control product (TSA value 42.5, drip time 3.2 seconds), and the finishing effect is not reduced due to the biodegradable design.

[0030] (3) Dual Quaternary Ammonium Synergy: Amide ammonium and dialkyl ammonium dual quaternary ammonium groups are also introduced into the biodegradable products to give full play to the synergistic effect of the two types of quaternary ammonium groups, ensuring that the products maintain excellent softness and hydrophilicity while being biodegradable.

[0031] (4) Environmentally friendly: After the product has been used for a period of time, it can be degraded into low molecular weight fragments in the wastewater treatment system, which significantly reduces its environmental persistence. At the same time, no low flash point solvents are required in the synthesis process, resulting in low VOC emissions, which meets the requirements of green chemistry and sustainable development.

[0032] (5) Compliance with regulatory trends: Meet the requirements of EU REACH and other regulations on substances of very high concern, and enhance the product’s access to international markets and competitiveness. Detailed Implementation

[0033] The present invention will be further described below through specific embodiments, but the scope of protection of the present invention is not limited thereto.

[0034] Example A biodegradable quaternized ABA block copolymer silicone oil with general formula (I) structure: XAB-A'-X' (I) in: B is a hydrophobic segment of a siloxane, containing the repeating unit shown in formula (II): B = [Si(R¹)(R²)O]_x; A and A' are hydrophilic spacer segments; X and X' are terminal quaternary ammonium groups; Characterized by the fact that the hydrophilic spacer segments A and A' are embedded with a degradable linking group L, wherein the degradable linking group is selected from at least one of the ester bond shown in formula (III), the acetal bond shown in formula (IV), or the carbonate bond shown in formula (V): ; ; ; in Selected from hydrogen atoms or C1-C6 alkyl groups; The degradable linker group causes the copolymer silicone oil to degrade into fragments with a molecular weight of less than 1000 Da under acidic conditions of pH 4.0-6.5 or in the presence of esterase.

[0035] Furthermore, the hydrophilic spacer segments A and A' are polycaprolactone-polyethylene glycol copolymer segments containing ester bonds, with the following structural formula: A = -(EO)_m-(CL)_n-; Where EO stands for ethylene oxide unit, CL stands for caprolactone unit, m is 5-30, and n is 1-20.

[0036] Furthermore, the X and X' terminal quaternary ammonium groups simultaneously comprise an amide ammonium group as shown in formula (VI) and a dialkyl ammonium group as shown in formula (VII): ; ; in Selected from C11-C23 straight-chain or branched, saturated or unsaturated alkyl groups. As an anion counterion; The molar ratio of the ammonium amide group to the dialkylammonium group is 9:1 to 6:4.

[0037] Furthermore, both R¹ and R² are methyl groups.

[0038] Furthermore, the biodegradable quaternized ABA block copolymer silicone oil exhibits a degradation rate of no less than 50% after 72 hours at pH 5.0 and 37°C.

[0039] Furthermore, the amine value of the biodegradable quaternized ABA block copolymer silicone oil is 2-60 mg KOH / g polymer.

[0040] A method for preparing degraded end-group quaternized ABA block copolymer silicone oil includes the following steps: Step (1): Using hydroxyl-terminated polycaprolactone-polyethylene glycol copolymer containing ester bonds as raw material, an allyl-terminated biodegradable polyether is prepared by reacting it with allyl glycidyl ether. The structural formula is as follows: ; Where m is 5-30 and n is 1-20; Step (2): In the presence of a platinum catalyst, the hydrogen-terminated silicone oil of formula (VIII) is subjected to a hydrogenation-silanization reaction with the allyl-terminated biodegradable polyether obtained in step (1) to obtain an epoxy silicone oil intermediate with biodegradable segments at the end groups: ; Where R¹ is methyl and x is 50-300; Step (3): The epoxy silicone oil intermediate and the tertiary amine are subjected to a ring-opening quaternization reaction in the presence of an acidic catalyst to obtain the degradable end-group quaternized ABA block copolymer silicone oil.

[0041] Furthermore, the tertiary amine in step (3) is a mixed tertiary amine of amide amine and dialkylolamine, wherein the amide amine has the structure shown in formula (IX) and the dialkylolamine has the structure shown in formula (X): ; ; in Selected from C11-C23 alkyl groups, Selected from C1-C10 alkyl groups; The molar ratio of amide amine to dialkylolamine in the mixed tertiary amine is 9:1 to 6:4.

[0042] Furthermore, the reaction temperature of step (1) is 60-100℃ and the reaction time is 4-12 hours; the hydrosilylation reaction temperature of step (2) is 70-120℃; and the ring-opening quaternization reaction temperature of step (3) is 70-110℃ and the reaction time is 4-24 hours.

[0043] A textile finishing agent composition comprising the aforementioned biodegradable terminal quaternized ABA block copolymer silicone oil, an emulsifier, and water.

[0044] I. Preparation Examples Example 1 (1) Preparation of allyl-terminated biodegradable polyether: Take 100 g of polycaprolactone-polyethylene glycol copolymer (HO-(EO)_10-(CL)_5-H, Mn≈1200 Da, prepared according to literature method), add 20 g of allyl glycidyl ether and catalyst. The reaction was carried out at 60-80℃ for 6 hours under nitrogen protection, and unreacted substances were removed by vacuum distillation (80℃, 1 mbar) to obtain allyl-terminated biodegradable polyether (epoxy value of about 0.035 mol / 100g).

[0045] (2) Preparation of epoxy silicone oil intermediates with degradable segments at the end groups: Take 2730 g of terminal hydrogen silicone oil (x=55, Si-H content 0.05 wt%, Wacker H polymer 55) (containing 1.3 mol of Si-H), add the allyl-terminated biodegradable polyether obtained in step (1) (containing 1.3 mol of allyl), heat to 95℃ under nitrogen protection, add 0.5 g of Pt catalyst, and react until the Si-H content is <2 ppm (NMR detection) to obtain epoxy silicone oil intermediate (epoxy value about 0.025 mol / 100g).

[0046] (3) Preparation of biodegradable quaternized ABA block copolymer silicone oil with end groups: Take the epoxy silicone oil intermediate obtained in step (2) (containing 0.0681 mol of epoxy groups), add amide amine (cocamidopropyl dimethylamine, Tegoamid® D5040, Evonik, 0.0477 mol) and N-methyldiethanolamine (0.0204 mol), add 0.0681 mol of acetic acid, and react at 80-100℃ for 8 hours under nitrogen protection. NMR detection showed that the epoxy group conversion rate was >98%. Remove the solvent and unreacted tertiary amine by vacuum distillation (100℃, 1 mbar) to obtain a biodegradable terminal quaternized ABA block copolymer silicone oil (Example 1), with an amine value of about 12 mg KOH / g and a viscosity of about 1200 mPa•s.

[0047] Example 2 The difference from Example 1 is that in step (1), polycaprolactone-polyethylene glycol copolymer HO-(EO)_15-(CL)_8-H (Mn≈1800 Da) is used, while the other conditions are the same, resulting in Example 2.

[0048] Example 3 The difference from Example 1 is that the molar ratio of amide amine to N-methyldiethanolamine in step (3) is 9:1, while the other conditions are the same, thus obtaining Example 3.

[0049] Example 4 The difference from Example 1 is that the molar ratio of amide amine to N-methyldiethanolamine in step (3) is 6:4, while the other conditions are the same, thus obtaining Example 4.

[0050] Comparative Example 1 The difference from Example 1 is that in step (1), polyethylene glycol (HO-(EO)_10-H, Mn≈500 Da) without ester bonds is used instead of polycaprolactone-polyethylene glycol copolymer, and the other conditions are the same, to obtain Comparative Example 1 (without degradable linking groups).

[0051] Comparative Example 2 The difference from Example 1 is that in step (3), only 0.0681 mol of amide amine was used, and N-methyldiethanolamine was not used. All other conditions were the same, resulting in Comparative Example 2.

[0052] II. Performance Testing Degradation performance test method: Take 1 g of each product prepared in Examples 1 to 4 and Comparative Example 1, and place them in 100 mL of phosphate-buffered saline (PBS) at pH 5.0, pH 6.5, and pH 7.4, respectively, and shake at 37°C (100 rpm) for 72 hours. Samples were taken periodically (0 h, 24 h, 48 h, 72 h), and molecular weight changes were analyzed using GPC (gel permeation chromatography) to calculate the degradation rate. {Degradation rate} = {Mn_0 - Mn_t}{Mn_0} * 100% Where Mn_0 is the initial number-average molecular weight, and Mn_t is the number-average molecular weight after degradation for time t.

[0053] Application performance testing: The same method as in the first patent application example is used to test softness (TSA value) and hydrophilicity (drip time).

[0054] Test results:

[0055] Results analysis: (1) Degradation performance: Examples 1 to 4 (containing ester-bonded degradable groups) showed a degradation rate exceeding 80% after 72 hours at pH 5.0, with the degradation product Mn < 1000 Da; the degradation rate was approximately 45-49% at pH 6.5, and < 10% at pH 7.4 (neutral). This indicates that the product of the present invention can rapidly degrade under acidic conditions (such as wastewater treatment environments) while remaining stable under neutral usage conditions (such as textile storage and use), achieving the ideal performance curve of "stable during use and degradable after disposal". Comparative Example 1 (without degradable groups) showed a degradation rate of < 5% under all pH conditions, verifying the necessity of the degradable linker group.

[0056] (2) Application performance: The softness (TSA value 40.0-41.8) and hydrophilicity (drip time 2.9-4.8 seconds) of Examples 1 to 4 were comparable to those of Comparative Example 1 (without degradable groups, TSA value 42.5, drip time 3.2 seconds), indicating that the introduction of degradable linking groups did not have a significant negative impact on the finishing performance. The hydrophilicity of Comparative Example 2 (ammonium amide only, without quaternary ammonium synergy) was significantly worse (drip time 8.2 seconds), verifying the necessity of the quaternary ammonium synergistic design.

[0057] Working principle: First aspect: This invention provides a biodegradable quaternized ABA block copolymer silicone oil with general formula (I): XAB-A'-X' (I); Where B is a hydrophobic segment of siloxane, containing the repeating unit shown in formula (II): B = [Si(R¹)(R²)O]_x (II); A and A' are hydrophilic spacer segments; X and X' are terminal quaternary ammonium groups; The hydrophilic spacer segments A and A' contain a degradable linker group L, which is selected from at least one of the ester bond shown in formula (III), the acetal bond shown in formula (IV), or the carbonate bond shown in formula (V). ; ; ; in Selected from hydrogen atoms or C1-C6 alkyl groups; The degradable linker group causes the copolymer silicone oil to degrade into fragments with a molecular weight of less than 1000 Da under acidic conditions of pH 4.0-6.5 or in the presence of esterase.

[0058] In a preferred embodiment of the present invention, the hydrophilic spacer segments A and A' are polycaprolactone-polyethylene glycol copolymer segments containing ester bonds, with the following structural formula: A = -(EO)_m-(CL)_n-; Where EO stands for ethylene oxide unit, CL for caprolactone unit, m is 5-30, and n is 1-20. The polycaprolactone segment provides degradable ester bonds, while the polyethylene glycol segment provides hydrophilicity and flexibility. When n=0, there are no ester bonds, and the product is non-degradable; when n>20, the degradable segments are too long and may affect emulsion stability; a balance between hydrophilicity and degradability is achieved when m=5-30.

[0059] In a preferred embodiment of the invention, the X and X' terminal quaternary ammonium groups simultaneously comprise an amide ammonium group as shown in formula (VI) and a dialkyl ammonium group as shown in formula (VII): ; ; in Selected from C11-C23 straight-chain or branched, saturated or unsaturated alkyl groups. It is an anionic counterion. The molar ratio of the ammonium amide group to the dialkylammonium group is 9:1 to 6:4, preferably 7:3.

[0060] In a preferred embodiment of the present invention, the degree of polymerization x of the B siloxane segment is 50-300, preferably 80-160, and the viscosity at 25°C is 100-15000 mPa•s.

[0061] In a preferred embodiment of the present invention, the biodegradable quaternized ABA block copolymer silicone oil has a degradation rate of not less than 50% after 72 hours under conditions of pH 5.0 and 37°C.

[0062] In a preferred embodiment of the present invention, the amine value of the biodegradable quaternized ABA block copolymer silicone oil is 2-60 mg KOH / g polymer.

[0063] The second aspect: This invention provides a method for preparing the aforementioned biodegradable quaternized ABA block copolymer silicone oil, comprising the following steps: Step (1) Using hydroxyl-terminated polycaprolactone-polyethylene glycol copolymer (HO-(EO)_m-(CL)_n-H) containing ester bonds as raw material, an allyl-terminated biodegradable polyether is prepared by reacting it with allyl glycidyl ether in the presence of an alkaline catalyst. The structural formula is as follows: ; Where m is 5-30 and n is 1-20.

[0064] Step (2) In the presence of a platinum catalyst, the hydrogen-terminated silicone oil of formula (VIII) is subjected to a hydrogenation-silanization reaction with the allyl-terminated biodegradable polyether obtained in step (1) to obtain an epoxy silicone oil intermediate with biodegradable segments at the end groups:

[0065] Where R¹ is methyl and x is 50-300.

[0066] Step (3) The epoxy silicone oil intermediate and the tertiary amine are subjected to a ring-opening quaternization reaction in the presence of an acidic catalyst to obtain the degradable end-group quaternized ABA block copolymer silicone oil.

[0067] In a preferred embodiment of the method of the present invention, the tertiary amine in step (3) is a mixed tertiary amine of amide amine and dialkylolamine, with a molar ratio of 9:1 to 6:4, preferably 7:3.

[0068] In a preferred embodiment of the method of the present invention, the number average molecular weight of the biodegradable polyether in step (1) is 500-3000 Da, preferably 800-2000 Da.

[0069] In a preferred embodiment of the method of the present invention, the reaction temperature of step (1) is 60-100℃, preferably 70-90℃, and the reaction time is 4-12 hours; the hydrosilylation reaction temperature of step (2) is 70-120℃, preferably 80-100℃; and the ring-opening quaternization reaction temperature of step (3) is 70-110℃, preferably 80-100℃, and the reaction time is 4-24 hours.

[0070] In a preferred embodiment of the method of the present invention, the acidic catalyst in step (3) is selected from at least one of acetic acid, lauric acid, isononanoic acid, and lactic acid, and the amount used is 0.5-2.0 times the molar number of the tertiary amine.

[0071] Third aspect: The present invention provides a textile finishing agent composition comprising the aforementioned biodegradable terminal quaternized ABA block copolymer silicone oil, emulsifier and water, wherein the silicone oil content is 5-40% by weight, the emulsifier content is 1-15% by weight, the water content is 45-94% by weight, and the pH is 4-7.

[0072] Fourth aspect: This invention provides the application of the aforementioned biodegradable terminal quaternized ABA block copolymer silicone oil in the softening, hydrophilicity and environmentally friendly finishing of textiles.

[0073] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

[0074] In summary, the above description is only a specific embodiment of the present invention, but the structural features of the present invention are not limited thereto. Any changes or modifications made by those skilled in the art within the scope of the present invention are covered by the patent scope of the present invention.

Claims

1. A biodegradable quaternized ABA block copolymer silicone oil with end groups having the general formula (I): XAB-A'-X' (I) in: B is a hydrophobic segment of a siloxane, containing the repeating unit shown in formula (II): B = [Si(R¹)(R²)O]_x; A and A' are hydrophilic spacer segments; X and X' are terminal quaternary ammonium groups; Characterized by the fact that the hydrophilic spacer segments A and A' are embedded with a degradable linking group L, wherein the degradable linking group is selected from at least one of the ester bond shown in formula (III), the acetal bond shown in formula (IV), or the carbonate bond shown in formula (V): ; ; ; in Selected from hydrogen atoms or C1-C6 alkyl groups; The degradable linker group causes the copolymer silicone oil to degrade into fragments with a molecular weight of less than 1000 Da under acidic conditions of pH 4.0-6.5 or in the presence of esterase.

2. The biodegradable quaternized ABA block copolymer silicone oil with end groups according to claim 1, characterized in that, The hydrophilic spacer segments A and A' are polycaprolactone-polyethylene glycol copolymer segments containing ester bonds, with the following structural formula: A = -(EO)_m-(CL)_n-; Where EO stands for ethylene oxide unit, CL stands for caprolactone unit, m is 5-30, and n is 1-20.

3. The biodegradable quaternized ABA block copolymer silicone oil with end groups according to claim 1, characterized in that, The X and X' terminal quaternary ammonium groups simultaneously include the amide ammonium group shown in formula (VI) and the dialkyl ammonium group shown in formula (VII): ; ; in Selected from C11-C23 straight-chain or branched, saturated or unsaturated alkyl groups. As an anion counterion; The molar ratio of the ammonium amide group to the dialkylammonium group is 9:1 to 6:

4.

4. The biodegradable quaternized ABA block copolymer silicone oil with end groups according to claim 1, characterized in that, Both R¹ and R² are methyl groups.

5. The biodegradable quaternized ABA block copolymer silicone oil with end groups according to claim 1, characterized in that, The biodegradable quaternized ABA block copolymer silicone oil exhibits a degradation rate of no less than 50% after 72 hours at pH 5.0 and 37°C.

6. The biodegradable quaternized ABA block copolymer silicone oil with end groups according to claim 1, characterized in that, The amine value of the biodegradable quaternized ABA block copolymer silicone oil is 2-60 mg KOH / g polymer.

7. A method for preparing the biodegradable quaternized ABA block copolymer silicone oil according to any one of claims 1 to 6, characterized in that, Includes the following steps: Step (1): Using hydroxyl-terminated polycaprolactone-polyethylene glycol copolymer containing ester bonds as raw material, an allyl-terminated biodegradable polyether is prepared by reacting it with allyl glycidyl ether. The structural formula is as follows: ; Where m is 5-30 and n is 1-20; Step (2): In the presence of a platinum catalyst, the hydrogen-terminated silicone oil of formula (VIII) is subjected to a hydrogenation-silanization reaction with the allyl-terminated biodegradable polyether obtained in step (1) to obtain an epoxy silicone oil intermediate with biodegradable segments at the end groups: ; Where R¹ is methyl and x is 50-300; Step (3): The epoxy silicone oil intermediate and the tertiary amine are subjected to a ring-opening quaternization reaction in the presence of an acidic catalyst to obtain the degradable end-group quaternized ABA block copolymer silicone oil.

8. The method according to claim 7, characterized in that, The tertiary amine in step (3) is a mixed tertiary amine of amide amine and dialkylolamine, wherein the amide amine has the structure shown in formula (IX) and the dialkylolamine has the structure shown in formula (X): ; ; in Selected from C11-C23 alkyl groups, Selected from C1-C10 alkyl groups; The molar ratio of amide amine to dialkylolamine in the mixed tertiary amine is 9:1 to 6:

4.

9. The method according to claim 8, characterized in that, The reaction temperature of step (1) is 60-100℃ and the reaction time is 4-12 hours; the reaction temperature of the hydrogenation silanization in step (2) is 70-120℃; the reaction temperature of the ring-opening quaternization in step (3) is 70-110℃ and the reaction time is 4-24 hours.

10. A textile finishing agent composition comprising the aforementioned degradable terminal quaternized ABA block copolymer silicone oil, an emulsifier, and water.

Citation Information

Patent Citations

  • Preparation method of solvent-free block silicone oil

    CN107522866A

  • Polyammonium modified polyether silicone oil, and preparation method and use thereof

    CN109535428A